A, The PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI MULTIMEDIA GUNA MENINGKATKAN MINAT LITERASI DAN NUMERASI BELAJAR ONLINE PESERTA DIDIK SEKOLAH DASAR: PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI MULTIMEDIA GUNA MENINGKATKAN MINAT LITERASI DAN NUMERASI BELAJAR ONLINE PESERTA DIDIK SEKOLAH DASAR - Febriana Sholikhah Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2021)
This study uses a Blended Learning model which is useful for increasing students' interest in numeracy literacy. Blended Learning model is learning with a model that is carried out with a combination of face-to-face and online learning systems. This method is useful for improving student literacy because by not only referring to online learning, students will get varied learning, students will be happier and more enthusiastic in learning if there are friends in the learning. With the application of game-based multimedia application media, it aims to increase students' literacy and numeracy interest, in addition to making learning not monotonous and students feel happy in learning and more fun than usual learning. Keywords: Multimedia Application, Numerical Literacy, Blended Learning.